Cancer surveillance in northern Africa, and central and western Asia: challenges and strategies in support of developing cancer registries. Issue 2 (February 2018) - Znaor, Ariana; Eser, Sultan; Anton-Culver, Hoda; Fadhil, Ibtihal; Ryzhov, Anton; Silverman, Barbara G; Bendahou, Karima; Demetriou, Anna; Nimri, Omar; Yakut, Cankut; Bray, Freddie
Summary: The Global Initiative for Cancer Registry Development partnership, led by the International Agency for Research on Cancer (IARC), was established in response to an overwhelming need for high-quality cancer incidence data from low-income and middle-income countries. The IARC Regional Hub for cancer registration in North Africa, Central and West Asia was founded in 2013 to support capacity building for cancer registration in each of the countries in this region. In this Series paper, we advocate the necessity for tailored approaches to cancer registration given the rapidly changing cancer landscape for this region, and the challenges faced at a national level in developing data systems to help support this process given present disparities in resources and health infrastructure. In addition, we provide an overview of the status of cancer surveillance and activities country-by-country, documenting tailored approaches that are informing local cancer-control policy, and potentially curbing the growing cancer burden across the region.